Tuning photoluminescence spectra of MoS2 with liquid crystals. Issue 39 (29th September 2021) - Yu, Jeong-Seon; Hwang, Jea-Jun; Lee, Jun-Yong; Ha, Dong Han; Kim, Jong-Hyun
Abstract : The liquid crystal texture on molybdenum disulfide (MoS2 ). And the photoluminescence and Raman spectra of MoS2 are shifted with liquid crystals. Abstract : The photoluminescence (PL) and Raman spectra of molybdenum disulfide (MoS2 ) can be tuned with liquid crystals. A nematic liquid crystal, 5CB, was aligned in a zigzag direction on an MoS2 monolayer flake. The PL and A1g Raman mode peaks of the MoS2 monolayer were shifted by 46 meV and 2 cm −1, respectively, owing to the interaction between MoS2 and the liquid crystal. Based on Lorentzian fitting analysis, it was confirmed that the peak positions and intensity ratios of the trion PL and exciton PL varied with the phase transition of the liquid crystal. This phenomenon was possibly caused by the transfer of electrons from MoS2 to the liquid crystal. This electron transfer varies with the temperature-dependent change in the liquid crystal phase. Therefore, the PL spectra of MoS2 can be tuned simply by controlling the phase, without changing the type of added material.